2020
DOI: 10.1108/gkmc-10-2019-0120
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the entrepreneurial orientation of the librarians

Abstract: Purpose The purpose of this study is to carry out the demographic evaluation and analysis of the entrepreneurial orientation of librarians in Iranian public libraries using the Lumpkin and Dess model. Design/methodology/approach In this study, a structured questionnaire of entrepreneurial orientation was used. The research population consisted of 5,000 librarians of Iranian public libraries who were selected using Krejcie and Morgan table (95% confidence level and p-value of 5%) and stratified the random sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…When considering each aspect, it was found that all aspects were at a high level. This may be because related to the research result of Doulani et al (2020), it was found that characteristics of entrepreneurship focus on three characteristics: autonomy, risk-taking, and competitive aggressiveness which affect competitive advantage. It is also related to Phimonrattanakan &Jesadalak's research (2019).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…When considering each aspect, it was found that all aspects were at a high level. This may be because related to the research result of Doulani et al (2020), it was found that characteristics of entrepreneurship focus on three characteristics: autonomy, risk-taking, and competitive aggressiveness which affect competitive advantage. It is also related to Phimonrattanakan &Jesadalak's research (2019).…”
Section: Discussionmentioning
confidence: 95%
“…Patcharachotsuthi (2018) the study found that competitive advantages include innovation, the difference in cost leadership, quick response, and focusing on specific business markets that affect the business's competitive advantage. Doulani et al (2020) found that entrepreneurs have four characteristics: autonomy orientation, risk-taking orientation, competitive aggressiveness orientation, and stability learning orientation affect the competitive advantage. Thurathamnon & Yodwisitsak (2022) found entrepreneurial attributes of self and competitive advantage.…”
Section: Research Hypothesismentioning
confidence: 99%
“…Results show that the risk-taking and innovative dimensions of entrepreneurship orientation influence the company's performance (Erista et al, 2020). Entrepreneurial orientation is one of the new branches of entrepreneurship which encompasses all the decision-making processes, procedures, and activities of the organization or company (Doulani et al, 2020). In a study conducted by Doulani et al (2020), it was found that entrepreneurial orientation is one of the significant concepts in the entrepreneurship of organizations.…”
mentioning
confidence: 99%
“…Entrepreneurial orientation is one of the new branches of entrepreneurship which encompasses all the decision-making processes, procedures, and activities of the organization or company (Doulani et al, 2020). In a study conducted by Doulani et al (2020), it was found that entrepreneurial orientation is one of the significant concepts in the entrepreneurship of organizations. Individuals with an entrepreneurship orientation could discover and explore new market opportunities (Galvão et al, 2020).…”
mentioning
confidence: 99%